The Discipline Enforcement at the Education and Culture Office of Lahat Regency - Meri Asyanti; Yusri Yusri; Amaludin Amaludin (Gayaku Publisher, 2022)
The Education and Culture Office of the Lahat Regency as an institution that provides services in the education sector seeks to improve personnel services to create professional, reliable, honest, clean, and responsible Civil Servants. The main problem in this study is